Answer:
546
Step-by-step explanation:
Multiples of 4 = 4 8 12 16 20 24 28 32 36 40 44 48
After Removing multiples of 6= 4 8 16 20 28 32 40 44
1.) Solve for x:
5 x + 7 = 3 x + 21
Subtract 3 x from both sides:
(5 x - 3 x) + 7 = (3 x - 3 x) + 21
5 x - 3 x = 2 x:
2 x + 7 = (3 x - 3 x) + 21
3 x - 3 x = 0:
2 x + 7 = 21
Subtract 7 from both sides:
2 x + (7 - 7) = 21 - 7
7 - 7 = 0:
2 x = 21 - 7
21 - 7 = 14:
2 x = 14
Divide both sides of 2 x = 14 by 2:
(2 x)/2 = 14/2
2/2 = 1:
x = 14/2
The gcd of 14 and 2 is 2, so 14/2 = (2×7)/(2×1) = 2/2×7 = 7:
Answer: x = 7
____________________________________________________________
2.) Solve for x:
3 x - 2 (5 - x) = 3 x - 3 (x - 10)
-2 (5 - x) = 2 x - 10:
2 x - 10 + 3 x = 3 x - 3 (x - 10)
Grouping like terms, 3 x + 2 x - 10 = (3 x + 2 x) - 10:
(3 x + 2 x) - 10 = 3 x - 3 (x - 10)
3 x + 2 x = 5 x:
5 x - 10 = 3 x - 3 (x - 10)
-3 (x - 10) = 30 - 3 x:
5 x - 10 = 30 - 3 x + 3 x
3 x - 3 x = 0:
5 x - 10 = 30
Add 10 to both sides:
5 x + (10 - 10) = 10 + 30
10 - 10 = 0:
5 x = 30 + 10
30 + 10 = 40:
5 x = 40
Divide both sides of 5 x = 40 by 5:
(5 x)/5 = 40/5
5/5 = 1:
x = 40/5
The gcd of 40 and 5 is 5, so 40/5 = (5×8)/(5×1) = 5/5×8 = 8:
<span>Answer: x = 8
_________________________________________________________
3.) Solve for x:</span>
5 (x + 1) = 3 (2 x + 3) + 5
3 (2 x + 3) = 6 x + 9:
5 (x + 1) = 6 x + 9 + 5
Grouping like terms, 6 x + 5 + 9 = 6 x + (9 + 5):
5 (x + 1) = 6 x + (9 + 5)
9 + 5 = 14:
5 (x + 1) = 6 x + 14
Expand out terms of the left hand side:
5 x + 5 = 6 x + 14
Subtract 6 x from both sides:
(5 x - 6 x) + 5 = (6 x - 6 x) + 14
5 x - 6 x = -x:
-x + 5 = (6 x - 6 x) + 14
6 x - 6 x = 0:
5 - x = 14
Subtract 5 from both sides:
(5 - 5) - x = 14 - 5
5 - 5 = 0:
-x = 14 - 5
14 - 5 = 9:
-x = 9
Multiply both sides of -x = 9 by -1:
(-x)/(-1) = -9
(-1)/(-1) = 1:
<span>Answer: x = -9</span>
Answer:
A is the answer
Step-by-step explanation:
What you do is you cross multiply 24x4 which equals 96. Then, you divide by 16. Which gives us: m = 6
Answer:
40 miles
Step-by-step explanation:
In the attached diagram, Point A is the starting point and C is the end point. We want to determine the distance from A to C.
The path driven forms a right triangle in which AC is the hypotenuse.
We therefore use the<u> Pythagorean Theorem</u> to solve for the AC.
Pythagorean Theorem: ![Hypotenuse^2=Opposite^2+Adjacent^2](https://tex.z-dn.net/?f=Hypotenuse%5E2%3DOpposite%5E2%2BAdjacent%5E2)
![|AC|^2=32^2+24^2\\|AC|^2=1600\\|AC|=\sqrt{1600}\\ |AC|=40$ miles](https://tex.z-dn.net/?f=%7CAC%7C%5E2%3D32%5E2%2B24%5E2%5C%5C%7CAC%7C%5E2%3D1600%5C%5C%7CAC%7C%3D%5Csqrt%7B1600%7D%5C%5C%20%7CAC%7C%3D40%24%20miles)
The straight line distance from the starting point is 40 miles.